Ultra-micro samples can be used for mRNA quantification of lung cancer biomarkers. (2nd April 2016) - Sandfeld-Paulsen, Birgitte; Demuth, Christina; Folkersen, Birgitte H.; Rasmussen, Torben R.; Madsen, Line B.; Sorensen, Boe S.; Meldgaard, Peter
ABSTRACT: Background Isolating sufficient material for molecular testing remains challenging in non-small cell lung cancer (NSCLC). The use of new ultra-microsamples (uMS) is proven sufficient for DNA and mRNA detection, but whether uMS are useful for quantifying mRNA expression is unknown. We investigated if uMS from lung cancer patients can be used to generate quantitative data on mRNA expression.Methods uMS were collected from primary tumors and lymph nodes from patients suspected of having lung cancer. mRNA was isolated, reverse-transcribed into cDNA and quantified with quantitative PCR assays for hepatocyte growth factor receptor ( MET ), hepatocyte growth factor ( HGF ), epidermal growth factor receptor ( EGFR ) and amphiregulin ( AREG ) mRNA. The fraction of tumor cells to normal cells was estimated in each sample.Results MET, HGF, EGFR, and AREG expression were evaluated in 90 samples (30 containing cancer cells and 60 without cancer cells). MET and EGFR expression were negligible in samples without cancer cells. In samples containing cancer cells, MET and EGFR could be quantified in 13 samples each. Adjustment for tumor-cell fraction made it possible to obtain a quantitative result for the tumor-cell mRNA expression of MET and EGFR . In contrast, AREG and HGF were expressed in samples without tumor cells. These samples were used to establish the AREG and HGF mRNA expression in normal cells. Seven out of 14 AR-positive and two out of eight HGF -positive samples with tumor cells were above a cut-off of the mean + 2SD established in samples without tumor cells.Conclusion We demonstrate that uMS contain high-quality mRNA, and quantitative studies can be performed when the tumor-cell fraction is considered.